PENGARUH RETURN ON EQUITY (ROE) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PADA PT. SURYA CITRA MEDIA TBK PERIODE 2013-2022 - Bila Ardani, Dwi; Janudin (Journal of Research and Publication Innovation, 2024)
The purpose of the study was to determine the effect of Return On Equity and Debt to Equity Ratio on Share Price at PT Surya Citra Media Tbk. both partially and simultaneously. The method used is quantitative method. The sample used is the financial statements in the form of balance sheets and income statements of PT Surya Citra Media Tbk. period 2013-2022. This research data analysis uses classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination analysis. The results of the research Return On Equity partially has a significant effect on Stock Price. Hypothesis testing obtained tcount> ttable value. Thus Ha1 is rejected and Ho1 is accepted, meaning that there is a partially significant effect between Return On Equity on Stock Price. Debt to Equity Ratio partially has no significant effect. Hypothesis testing found the value of tcount < ttable or. Thus Ha2 is rejected and Ho2 is accepted, meaning that there is no partially significant effect between Debt to Equity Ratio on Stock Price. Return On Equity and Debt to Equity Ratio simultaneously have a significant effect. Hypothesis testing obtained the value of Fcount> Ftable. Thus Ho3 is rejected and Ha3 is accepted, meaning that there is a significant influence between Return On Equity and Debt to Equity Ratio simultaneously on Stock Price.